Ethnicity and maternal and child health outcomes and service coverage in western China: a systematic review and meta-analysis - Yuan Huang; David Shallcross; Li Pi; Fan Tian; Jay Pan; Prof Carine Ronsmans (Elsevier, 2018)
Background: There is a dearth of accurate information about health outcomes and health service coverage among ethnic minorities in China. We assessed maternal and child health (MCH) outcomes and service coverage among ethnic minorities compared with Han populations in western China. Methods: We did a systematic review searching English (Embase, MEDLINE, Web of Science) and Chinese (China National Knowledge Infrastructure [CNKI], VIP, Wanfang) databases for population-based studies comparing MCH indicators between ethnic minorities between Jan 1, 1990, and Nov 9, 2016, in any language. For studies making individual comparisons we used the odds ratio (OR) and corresponding 95% CIs as the primary measure to assess the association between MCH indicators and ethnicity. We used a random-effects model to pool odds ratios. Findings: We included 29 Chinese and 16 English language studies, providing 31 individual comparisons and 15 ecological comparisons. Ethnic minority women had lower odds of antenatal care use (pooled crude OR 0·60 [95% CI 0·48-0·75]) and birth in health facilities (0·50 [0·39-0·64]) than did Han women; and their children had higher odds of mortality (2·02 [1·23-3·32]) and lower immunisation (0·34 [0·24-0·47]) than did Han children. After taking account of the potential confounding effects of socioeconomic factors, ethnic minority women were less likely to use antenatal care (pooled adjusted OR 0·54 [0·42-0·71]) or to immunise their children (0·57 [0·44-0·74]) compared with Han women. Interpretation: China has a wealth of primary data that could further our understanding of why ethnic minority populations are lagging behind. As MCH outcomes continue to improve nationally, ethnic minorities will take a greater share of the overall burden of adverse outcomes, requiring strategic investments to address the specific challenges faced by people living in remote areas. Funding: China Medical Board.